Physical activity to improve health: do not forget that the lungs benefit too. Issue 2 (1st February 2018) - Puente-Maestu, Luis; Stringer, William W.
In this issue of the European Respiratory Journal, Hancox and Rasmussen [1], present an analysis of data from two cohorts, one from Denmark and the other from New Zealand, demonstrating that, in cross-sectional analyses at all ages in both cohorts, aerobic fitness during the childhood and adolescence period was positively associated with forced expiratory volume in 1 s (FEV1 ) and forced vital capacity (FVC) (figures 1 and 2). This association persisted despite independently adjusting for height, weight, sex, current asthma and current smoking. Each standard deviation difference in fitness was associated with a modestly higher predicted values for FEV1 and FVC (2–3%). Physically active children will enjoy better lung function in adulthood http://ow.ly/P1Pk30hFIPS